A VISÃO DO PROFESSOR DE ALGUMAS ESCOLAS MUNICIPAIS DE VALENÇA-BAHIA REFERENTE AO LIVRO VONTADE DE SABER DO SEXTO ANO - de Sousa Pereira, Taniele; Silva Teixeira, Leandro (LINKSCIENCEPLACE, 2026)
In the case of mathematics, most students show difficulties in understanding the contents. With prime numbers it is no different, perhaps because the student is not aware of their importance and how much these numbers are part of their daily life. In this context, this article seeks to understand how the aforementioned content in the textbook of Elementary School II, chosen by the Municipal Council of Education of Valencia-BA, is approached. The book is part of the collection: "Will to Know - Mathematics" by Joamir Prado and Patrícia Moreno Pataro for the years 2017, 2018 and 2019. The collection was approved in accordance with the guidelines of the National Curricular Parameters (NCPs), a document prior to the approval of the National Curricular Common Base (BNCC). This paper also presents the historical context, the importance, the analysis of the authors and the vision of some teachers of the schools of the mentioned municipality through the application of questionnaires.